An Opportunity for Improving Osteoporosis Treatment in Home Health Care - Switzer, Julie A. (SAGE Publications, 2010)
Purpose: To examine osteoporosis prevention and treatment among home health care (HHC) patients at risk of fragility fracture in a large, Midwestern integrated HHC system. Methods: All patients who received HHC services in 2006 were identified. International Classification of Diseases, Ninth Revision (ICD-9) diagnosis codes and pharmaceutical data were examined between January 1, 2004 and December 31, 2005 to determine risk status (high vs average) for fragility fracture. Patients with a documented diagnosis of osteoporosis, osteopenia, previous fragility fracture, stroke, or those taking a glucocorticoid were categorized as high risk. Pharmaceutical data (eg, estrogen, bisphosphonates) were obtained during the same 2-year period to determine treatment status. Descriptive statistics documented the proportion at high risk and treatment status. Inferential statistics tested differences in characteristics (age, gender, race, number of comorbidities) among high-risk patients with and without treatment. Results: 2798 patients were seen in HHC during 2006 and had utilization data available in 2004 and 2005. Of these, 754 were categorized as high risk and 2044 as average risk. Approximately one third (34%) of high-risk patients received osteoporosis medication compared to 4% of average risk (P < .0001). We found no treatment differences based on age. Those with higher comorbidity profiles were less likely to receive treatment (P < .0001). Conclusion: Only 34% of HHC patients at high risk for fracture received adequate treatment. Patients with more comorbidities were least likely to receive treatment. Since these individuals are receiving medical and nursing care, an opportunity exists to increase treatment rates for those at greatest risk.